Natural rubber modification by vinyl monomers grafting: a review - Supat Moolsin; Nikki K. Robishaw (Journal of Current Science and Technology, 2015)
This review article provides information on chemical modification of natural rubber (NR) by grafting with hydrophilic or hydrophobic vinyl monomers, involving a free radical polymerization on the backbone of the rubber. Graft copolymer can be generated from a latex, solvent, or monomer medium using a variety of initiation systems. Key processing parameters consist of monomer to rubber ratio, type of initiator, initiator concentration, reaction temperature and time. Characterization techniques such as Fourier transform infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry (MS), and transmission electron microscopy (TEM) are presented. The properties of the graft product such as grafting efficiency, conversion, molecular weight, thermal property, mechanical properties, oil resistance, water absorption, and phase morphology are discussed. The review also includes the applications of the presented graft copolymers.